Westernization of 'Darülfünun' and its Impacts on Religious Education in Turkish Universities - Siddiq, Ahmad; Haqq, Syauqy Arinal (AT-TURATS, 2023)
This study aims to elaborate on and examine Westernization at the first modern university in the Muslim world called Darülfünun and its impact of on religious education in Turkish universities. The study explores the history of the establishment of Darülfünun at the beginning to determine some efforts to Westernize this institution. This research is qualitative with an approach to library study. Data is collected through documentation such as books, articles, and educational policies of the Turkish government over a certain period. This study revealed that Darülfünun, which has now changed its name to Istanbul University, has held several Westernization agendas and inevitably influenced religious education conducted by the other Faculty of Theology in Turkish universities. The secularization and modernization ordered by Atatürk played a significant role in shaping the Turkish educational system. Due to its status as a pioneer of modern universities in Türkiye, Darülfünun has inspired modernization as well as Westernization in universities founded throughout the country.